Profete in Israel: "n Probleemstelling - Deist, Ferdinand (Hervormde teologiese studies, 1990)
Prophets in Israel: Stating a problem The Writing Prophets have, in Christian circles, traditionally been painted in a fairly romantic light as the giants of faith. A comparison between the superscriptions of the prophetic books and the historical literature of the Old Testament as well between the Jewish, Samaritan and Christian traditions’ views of the prophets raises several questions regarding the ‘office’ of the prophets, their social role and the notion of the church’s ‘prophetic’ calling. In the light of these questions the article calls for a fresh historical look at the Writing Prophets and identifies a few problem areas that may warrant further investigation.